Hospital differences in special care nursery use for newborns of gestational diabetic mothers. (16th September 2016) - Danilack, Valery A.; Muri, Janet H.; Savitz, David A.; Caldwell, Donna L.; Wood, Carolyn L.
Abstract: Objective : Relatively healthy newborns of mothers with gestational diabetes mellitus (GDM) sometimes receive unwarranted surveillance. We studied the relationship between hospital characteristics and special care nursery use and total length of stay among GDM deliveries. Methods : We identified GDM deliveries at 44 USA member hospitals of the National Perinatal Information Center from 2007 to 2011. To study low risk, relatively healthy newborns with presumed discretion in special care nursery use, we analyzed 43 444 singleton newborns with only minor or moderate complications and WHO were not preterm or low birthweight. Results : Among eligible newborns, 6% received special care, but this ranged from 1% to 16% across 44 hospitals studied. Unadjusted associations suggested special care nursery use was highest in academic teaching hospitals, the Midwest, hospitals with ≥40% Medicaid births, and hospitals with a high supply of special care nursery beds. However, after controlling for clustering within hospitals, there were no significant associations between hospital characteristics and special care nursery use or length of stay. Conclusions : Hospital-level variation in special care nursery use and length of stay of relatively healthy newborns of mothers with GDM is unexplained by hospital characteristics and suggests other operational or management factors impacting utilization of newborn care resources.